Homodimerization and constitutive activation of the erythropoietin receptor. - Watowich, S S (1992)
The erythropoietin receptor (EPO-R) is a member of the recently described cytokine receptor superfamily. A constitutively active (hormone independent) form of the EPO-R was isolated that has a single amino acid change in the exoplasmic domain, converting arginine-129 to cysteine (R129C). Since EPO-Rs containing R129S, R129E, and R129P mutations are functionally wild type, the presence of cysteine at residue 129, and not the loss of arginine, is required for constitutive activity. Several mutant forms of the EPO-R were analyzed; all constitutively active mutants form disulfide-linked homodimers, whereas EPO-responsive or inactive forms of the receptor do not. Monomers and disulfide-linked dimers of the constitutive receptor are present on the plasma membrane and bind EPO with a single affinity. Homodimerization of the EPO-R is likely to play a role in ligand-induced signal transduction, and disulfide-linked dimerization of the constitutive receptor may mimic this step.